2018
DOI: 10.1073/pnas.1717904115
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic polydnavirus and venom reveal parasitoid to its hyperparasitoids

Abstract: Symbiotic relationships may provide organisms with key innovations that aid in the establishment of new niches. For example, during oviposition, some species of parasitoid wasps, whose larvae develop inside the bodies of other insects, inject polydnaviruses into their hosts. These symbiotic viruses disrupt host immune responses, allowing the parasitoid's progeny to survive. Here we show that symbiotic polydnaviruses also have a downside to the parasitoid's progeny by initiating a multitrophic chain of interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 35 publications
0
59
0
2
Order By: Relevance
“…In certain contexts, there may be costs associated with PDV manipulation of host plant defenses. The benefits to parasitoid fitness provided by PDVs could be mitigated in circumstances where hyperparasitoids may more easily locate their parasitoid hosts through changes in herbivore-induced plant volatiles ( 36 ). Nevertheless, these studies reveal that PDVs play far more prominent roles in shaping plant–herbivore interactions across multiple trophic levels than previously understood.…”
Section: Resultsmentioning
confidence: 99%
“…In certain contexts, there may be costs associated with PDV manipulation of host plant defenses. The benefits to parasitoid fitness provided by PDVs could be mitigated in circumstances where hyperparasitoids may more easily locate their parasitoid hosts through changes in herbivore-induced plant volatiles ( 36 ). Nevertheless, these studies reveal that PDVs play far more prominent roles in shaping plant–herbivore interactions across multiple trophic levels than previously understood.…”
Section: Resultsmentioning
confidence: 99%
“…An intriguing parallel with our system has been reported in recent studies documenting differences in plant defence responses to caterpillars infected with parasitoid wasps and their symbiotic polydnaviruses compared to uninfected caterpillars. While one study identified suppression of plant defences that benefitted the parasitoid, another study reported changes in HIPVs that betrayed parasitoids to their hyperparasitoids (Tan et al, ; Zhu et al, ). These findings provide further evidence that organisms at the third trophic level and their associated symbionts can influence plant responses, which sometimes benefit and are sometimes detrimental for the natural enemies.…”
Section: Discussionmentioning
confidence: 99%
“…This may result from parasitoid infection modifying host's immune (Tan et al, 2018) or metabolic (Potter and Woods, 2012;Mrinalini et al, 2015) homeostasis that can further influence the intestinal microbial community. Several studies have recently reported an impact of polydnaviruses injected in the caterpillars through the venoms of parasitoid wasps Tan et al, 2018;Zhu et al, 2018). These symbiotic viruses induce changes in the caterpillar-plant interactions as well as in host immunity.…”
Section: Sex and Parasitoid Infection Are Correlated With Variation Omentioning
confidence: 99%